Analysis of Family Support and Reinforcement on Work Stress of Health Officers at Public Health Center Batang-Batang District Sumenep - Ceria Antika; Ratna Wardani (Journal for Quality in Public Health, 2022)
Stress is a common problem in modern life, including work-related stress. The purpose of this study is to analyze influence family support and reinforcement of the work stress of health workers in Public health center Batang-Batang District, Sumenep. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzing influence family support and reinforcement of the work stress of health workers in Public health center Batang-Batang District, Sumenep. The total population of 137 respondents and a sample of 102 respondents were taken using the Simple Random Sampling technique. In this study, it was found that most of the respondents had good family support as many as 53 respondents (52%). Almost half of the respondents have reinforcement in the good category as many as 41 respondents (40%). Most of the respondents have work stress in the low category as many as 46 respondents (45%).Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so it can be concluded that simultaneously there is influence family support and reinforcement of the work stress of health workers in Public health center Batang-Batang District, Sumenep with a magnitude of influence of 79.5%. It is expected that respondents can maintain a positive self-assessment and calm the mind in various ways such as meditation and relaxation. As well as carrying out activities outside of work such as recreation or other forms of entertainment to relieve the effects of stress generators in the workplace.